Decade of the Dacoits - Sahito, Imdad Hussain 1960-; Introduction by Ansari, Sarah (Karachi Oxford University Press, 2005)
With special reference to Sindh, Pakistan.
Include Maps and Illustrations, Bibliography and Index
Keywords: Pakistan--Sindh -- Dacoits